Conductivity Degradation of Polyvinylidene Fluoride Composite Binder during Cycling: Measurements and Simulations for Lithium-Ion Batteries. Issue 9 (2nd July 2016) - Grillet, Anne M.; Humplik, Thomas; Stirrup, Emily K.; Roberts, Scott A.; Barringer, David A.; Snyder, Chelsea M.; Janvrin, Madison R.; Apblett, Christopher A.
Abstract : The polymer-composite binder used in lithium-ion battery electrodes must both hold the electrodes together and augment their electrical conductivity while subjected to mechanical stresses caused by active material volume changes due to lithiation and delithiation. We have discovered that cyclic mechanical stresses cause significant degradation in the binder electrical conductivity. After just 160 mechanical cycles, the conductivity of polyvinylidene fluoride (PVDF):carbon black binder dropped between 45–75%. This degradation in binder conductivity has been shown to be quite general, occurring over a range of carbon black concentrations, with and without absorbed electrolyte solvent and for different polymer manufacturers. Mechanical cycling of lithium cobalt oxide (LiCoO2 ) cathodes caused a similar degradation, reducing the effective electrical conductivity by 30–40%. Mesoscale simulations on a reconstructed experimental cathode geometry predicted the binder conductivity degradation will have a proportional impact on cathode electrical conductivity, in qualitative agreement with the experimental measurements. Finally, ohmic resistance measurements were made on complete batteries. Direct comparisons between electrochemical cycling and mechanical cycling show consistent trends in the conductivity decline. This evidence supports a new mechanism for performance decline of rechargeable lithium-ion batteries during operation – electrochemically-induced mechanical stresses that degrade binder conductivity, increasing the internal resistance of the battery with cycling.